PREREQUISITES AND MAIN CAUSES OF POPULAR UPRISINGS AND PROTESTS IN THE AKTOBE REGION IN THE 1920s–1930s (Journal of history, 2026)
Introduction. This article provides a historical overview and analysis of popular uprisings and protests that took place in the Aktobe region in the 1920s–1930s in response to the excesses of Soviet government policies in the political, economic, and spiritual spheres. Aim of the study. Based on previously published historical studies on this topic, as well as previously unpublished archival materials and other sources, the study aims to analyze the prerequisites and causes of the emergence of uprisings and protests. The objectives derived from this aim include the systematization of diverse data and materials; classification and grouping of uprisings and protests according to their causes; analysis of the driving forces and social composition of participants; and the assessment and formulation of conclusions regarding the political, social, and spiritual situation of the 1920s–1930s based on the analysis of historiographical and archival materials. Materials and methods. The article is based on previously published works by domestic and foreign researchers, as well as materials from the Aktobe Regional Archive. The methods employed include the classification of popular uprisings and protests that occurred in the Aktobe region in the 1920s–1930s according to their causes; classification by geographical scope; social analysis of the participants’ composition; and evaluation of events from historical, sociological, political, cultural, and spiritual perspectives. Results. On the basis of the applied methods, it was clarified and systematized that the actions of the Soviet authorities, reflecting the characteristics of the historical era (forced collectivization, sedentarization, anti-religious campaigns, great-power chauvinism, the creation of social divisions, etc.), led to mass popular unrest, and these processes were critically assessed. The study also identifies and highlights issues that may serve as a logical continuation of this topic in future research on national history. It is proposed to classify these issues according to the prerequisites of uprisings and protests.
Keywords: popular uprisings, public discontent, archival materials, forced collectivization.